Fretting wear properties of Inconel600 alloy at high temperature - XIN Long; MA Miao; LU Yong-hao (工程科学学报, 2015)
Fretting test was carried out using an SRV-Ⅳ fretting test rig in order to investigate the fretting behavior and mechanism of Inconel 600 alloy at high temperature. The results indicate that high temperature is beneficial to the formation of an adhesion zone,but restrain the generation of a micro-sliding zone. The friction coefficient and wear loss decrease with the increase of temperature. Friction oxidation mainly occurs in the sliding zone of wear scars,while there is little oxidation in the adhesion zone. Oxygen concentration in the sliding zone at high temperature is more obvious than that at room temperature. At the center of the adhesion region,the oxygen content is low and there is a lot of single Ni,Cr and Fe. At the wear scar surface,the oxides are composed of NiO,Cr2O3 and Fe3O4. At both room temperature and high temperature,microcracks are usually found in the sliding/adhesion junction zone,while the position of crack initiation at high temperature is in the micro-sliding zone. However,the number and length of cracks at high temperature are less than those at room temperature.